Study on the Ethical Perceptions of Accounting Students: Evidence from Medan City - Nainggolan, Edisah Putra (AIBPM Publisher, 2023)
This study aims to assess the ethical behavior of accounting students in the city of Medan. The ethical perceptions of accounting students in Medan City will be examined with the Love of Money variable, which is influenced by variables such as Machiavellian behavior, religiosity, and gender. The research approach employed in this study is explanatory. The population of interest consists of accounting students enrolled in state universities in Medan City. A random sample of 100 respondents was selected for the study. The data analysis method utilized is Structural Equation Modeling (SEM) analysis. The discussion of the results reveals that Machiavellian behavior influenced students' ethical perceptions. Additionally, the study found that religiosity and gender both have an impact on students' ethical perceptions. However, based on the data analysis, it was determined that the Love of Money variable does not serve as an intervening variable.